Bathyal octopus, Muusoctopus leioderma, living in a world of acid: First recordings of routine metabolic rate and critical oxygen partial pressures of a deep water species under elevated pCO2 - Trueblood, Lloyd A.; Onthank, Kirt; Bos, Noah; Buller, Lucas; Coast, Arianna; Covrig, Michael; Edwards, Ethan; Fratianni, Stefano; Gano, Matthew; Iwakoshi, Nathaniel; Kim, Eden; Moss, Kyle; et al. (Frontiers in Physiology, 2022)
Elevated atmospheric CO2 as a result of human activity is dissolving into the world’s oceans, driving a drop in pH, and making them more acidic. Here we present the first data on the impacts of ocean acidification on a bathyal species of octopus Muusoctopus leioderma. A recent discovery of a shallow living population in the Salish Sea, Washington United States allowed collection via SCUBA and maintenance in the lab. We exposed individual Muusoctopus leioderma to elevated CO2 pressure (pCO2) for 1 day and 7 days, measuring their routine metabolic rate (RMR), critical partial pressure (Pcrit), and oxygen supply capacity (α). At the time of this writing, we believe this is the first aerobic metabolic data recorded for a member of Muusoctopus. Our results showed that there was no change in either RMR, Pcrit or α at 1800 µatm compared to the 1,000 µatm of the habitat where this population was collected. The ability to maintain aerobic physiology at these relatively high levels is discussed and considered against phylogeny and life history.